Hypodontia prevalence and distribution pattern in a group of Qatari orthodontic and pediatric patients: A retrospective study - Al Jawad, Feras H. Abed; Al Yafei, Hanan; Al Sheeb, Muneera; Al Emadi, Buthaina; Al hashimi, Najah (European Journal of Dentistry, 2015)
Objectives: The aim of this study was to investigate the prevalence and distribution of hypodontia in the permanent teeth among a group of the Qatari sample and to compare the present results with findings from other populations. Materials and Methods: Records of 1269 Qatari patients (674 females; mean age 11.8 ± 2.3 and 595 males; mean age 11.4 ± 2.2) which included panoramic radiographs were examined to identify hypodontia. All permanent teeth were investigated except third molars. Results: The prevalence of hypodontia was 6.2% (females 8% and males 4.2%; P < 0.05). The majority of patients had one or two missing teeth. There were no significant differences between right and left sides for any particular tooth. The most frequently missing teeth were maxillary lateral incisors (36.2%), followed by mandibular second premolar (32.6%) and maxillary second premolar (20.2%). Hypodontia was more commonly found unilaterally than bilaterally (63.2% and 44.3%; respectively). Conclusions: The prevalence of hypodontia in a group of the Qatari population was within the average value of the majority of published studies in the literature. Hypodontia was significantly more prevalent in females. Although less prevalent, considerable cases of bilateral missing were found in the present study, which necessitates the urgent need for intervention and multi-disciplinary team approach for management.
Keywords: Hypodontia; patient; prevalence; Qatari